Analysis of the Effect of Peristaltic Transport Flux on Channel Wall: Bingham Fluid as A Model - Al-Khafajy, Dheia G. Salih; Bribesh, Fathi Ali M; Thoubaan, Mary Ghadbaan (Iraqi Journal of Science, 2024)
This study is concerned with analyzing the peristaltic flow of Bingham fluid through an irregular tube with a short wavelength “relative to channel width” and using the governing equations of Bingham fluid in the Navier-Stokes equations in the Cartesian coordinate system. Significant results of the problem were obtained and analyzed using the Wolfram-Mathematica Computational Notebook.